Hubungan tingkat pengetahuan ibu dengan perilaku penanganan demam pada balita - Fitria, Nadira Jihan; Arifah, Siti (Holistik Jurnal Kesehatan, 2024)
Background: Fever is a normal response to many conditions, most commonly infection; no other value is defined as fever. Fever generally occurs when there is an increase in temperature caused by an increase in the temperature-regulating center in the hypothalamus. The mother's role is very important in caring for a child who has a fever. The mother's knowledge is needed so that the actions given are correct or not, such as how you determine if the child has a fever and when you take him to a health worker. Purpose: To determine the relationship between mothers' level of knowledge and fever handling behavior in toddlers. Method: This research is a quantitative study with a cross-sectional design. The population of this study was 216 people, with a sample of 68 mothers taken using a proportionate stratified random sampling technique and an instrument in the form of a questionnaire on the level of control and fever management behavior. Data on respondents' level of knowledge and fever handling behavior were collected using a questionnaire and analyzed using the Kendall’s-Tau test. Results: Showed that the level of knowledge of mothers about fever was mostly in the good category, namely 58 mothers (85.3%). Most mothers' behavior in treating fever was in the good category, namely 61 mothers (89.7%). The Kendall’s-Tau test on the level of knowledge and behavior of treating fever of respondents showed a p value of 0.000 or smaller than α = 0.05. Conclusion: There is a significant relationship between the level of fever knowledge and fever management behavior in children under five.   Keywords: Fever; Fever Management Behavior; Knowledge Level; Mother.   Pendahuluan: Demam merupakan respon normal untuk berbagai kondisi, yang paling umum dari infeksi, tidak ada nilai lain yang didefinisikan sebagai demam. Demam umumnya terjadi ketika adanya peningkatan suhu disebabkan oleh peningkatan pusat pengatur suhu di hipotalamus. Peran ibu sangat penting dalam merawat anak yang sedang demam, pengetahuan ibu diperlukan agar tindakan yang diberikan itu benar atau tidak seperti cara ibu menentukan anak demam dan kapan ibu membawa ke petugas kesehatan. Tujuan: Untuk mengetahui hubungan tingkat pengetahuan ibu dengan perilaku penanganan demam pada balita. Metode: Penelitian kuantitatif dengan rancangan cross sectional. Sampel penelitian berjumlah 68 orang ibu yang diambil menggunakan teknik proportionate stratified random sampling dengan instrumen berupa kuesioner tingkat pengetahuan dan perilaku penanganan demam. Data tingkat pengetahuan dan perilaku penanganan demam responden dikumpulkan menggunakan kuesioner dan dianalisis menggunakan uji Kendall’s-Tau. Hasil: Menunjukkan bahwa tingkat pengetahuan ibu tentang demam sebagian besar dalam kategori baik yaitu sebanyak 58 ibu (85.3%). Perilaku ibu dalam penanganan demam Sebagian besar dalam kategori baik yaitu sebanyak 61 ibu (89.7%). Uji Kendall’s-Tau terhadap tingkat pengetahuan dan perilaku penanganan demam responden menunjukkan p value = 0.000 atau lebih kecil dari α = 0.05. Simpulan Terdapat hubungan yang signifikan antara hubungan tingkat pengetahuan demam dengan perilaku penanganan demam pada anak balita..   Kata Kunci: Demam; Ibu; Perilaku Penanganan Demam; Tingkat Pengetahuan.